The Counter-Reformation in Central Europe Styria, 1580-1630 - Portner, Regina (Oxford historical monographs., 2001)
This is an account of religious belief and conflict in the strategically important province of Inner Austria between 1580 and 1630. Dr Portner analyses the aims, achievements, and shortcomings of the Habsburgs' confessional crusade in Styria.